Role of central kisspeptin and RFRP‐3 in energy metabolism in the male Wistar rat. (7th May 2021) - Cázarez‐Márquez, Fernando; Eliveld, Jitske; Ritsema, Wayne I. G. R.; Foppen, Ewout; Bossenbroek, Yvonne; Pelizzari, Simone; Simonneaux, Valérie; Kalsbeek, Andries
Abstract: Kisspeptin (Kp) and (Arg)(Phe) related peptide 3 (RFRP‐3) are two RF‐amides acting in the hypothalamus to control reproduction. In the past 10 years, it has become clear that, apart from their role in reproductive physiology, both neuropeptides are also involved in the control of food intake, as well as glucose and energy metabolism. To investigate further the neural mechanisms responsible for these metabolic actions, we assessed the effect of acute i.c.v. administration of Kp or RFRP‐3 in ad lib. fed male Wistar rats on feeding behaviour, glucose and energy metabolism, circulating hormones (luteinising hormone, testosterone, insulin and corticosterone) and hypothalamic neuronal activity. Kp increased plasma testosterone levels, had an anorexigenic effect and increased lipid catabolism, as attested by a decreased respiratory exchange ratio (RER). RFRP‐3 also increased plasma testosterone levels but did not modify food intake or energy metabolism. Both RF‐amides increased endogenous glucose production, yet with no change in plasma glucose levels, suggesting that these peptides provoke not only a release of hepatic glucose, but also a change in glucose utilisation. Finally, plasma insulin and corticosterone levels did not change after the RF‐amide treatment. The Kp effects were associated with an increased c‐Fos expression in the median preoptic area and a reduction in pro‐opiomelanocortin immunostaining in the arcuate nucleus. No effects on neuronal activation were found for RFRP‐3. Our results provide further evidence that Kp is not only a very potent hypothalamic activator of reproduction, but also part of the hypothalamic circuit controlling energy metabolism. Abstract : In the past 10 years, it has become clear that apart from their role in reproductive physiology the RF‐amides Kisspeptin (Kp) and (Arg)(Phe) related peptide 3 (RFRP‐3) are also involved in the control of food intake, as well as glucose and energy metabolism. To investigate further the neural mechanisms responsible for these metabolic actions, we assessed the effect of acute i.c.v. administration of Kp or RFRP‐3 in ad lib. fed male Wistar rats on feeding behaviour, glucose and energy metabolism, circulating hormones (luteinising hormone, testosterone, insulin and corticosterone) and hypothalamic neuronal activity. Our results provide further evidence that Kp is not only a very potent hypothalamic activator of reproduction, but also part of the hypothalamic circuit controlling energy metabolism.